Subduction of Indian continent beneath southern Tibet in the latest Eocene (~35Ma): Insights from the Quguosha gabbros in southern Lhasa block - Ma, L.; Wang, Q.; Li, Zheng-Xiang; Wyman, D.; Yang, J.; Jiang, Z.; Liu, Y.; Gou, G.; Guo, H. (Elsevier BV, 2015)
Geophysical data illustrate that the Indian continental lithosphere has northward subducted beneath the Tibet Plateau, reaching the Bangong–Nujiang suture in central Tibet. However, when the Indian continental lithosphere started to subduct, and whether the Indian continental crust has injected into the mantle beneath southern Lhasa block, are not clear. Here we report new results from the Quguosha gabbros of southern Lhasa block, southern Tibet. LA-ICP-MS zircon U–Pb dating of two samples gives a ca. 35 Ma formation age (i.e., the latest Eocene) for the Quguosha gabbros. The Quguosha gabbro samples are geochemically characterized by variable SiO2 and MgO contents, strongly negative Nb–Ta–Ti and slightly negative Eu anomalies, and uniform initial 87Sr/86Sr (0.7056–0.7058) and εNd(t) (− 2.2 to − 3.6). They exhibit Sr–Nd isotopic compositions different from those of the Jurassic–Eocene magmatic rocks with depleted Sr–Nd isotopic characteristics, but somewhat similar to those of Oligocene–Miocene K-rich magmatic rocks with enriched Sr–Nd isotopic characteristics. We therefore propose that an enriched Indian crustal component was added into the lithospheric mantle beneath southern Lhasa by continental subduction at least prior to the latest Eocene (ca. 35 Ma). We interpret the Quguosha mafic magmas to have been generated by partial melting of lithospheric mantle metasomatized by subducted continental sediments, which entered continental subduction channel(s) and then probably accreted or underplated into the overlying mantle during the northward subduction of the Indian continent. Continental subduction likely played a key role in the formation of the Tibetan plateau at an earlier date than previously thought.